131 Coupled CAR® technology strengthens adoptive T cell therapy by promoting rapid expansion. (9th November 2020) - Cao, Zhiyuan; Pu, Chengfei; Jiang, Xianyang; Shen, Xiaogang; Zhu, Ruihong; Peng, Yuzhe; Huang, Xi; Wu, Zhao; Xiao, Lei
Abstract : Background: CAR T therapy has achieved remarkable results in the treatment of hematological tumors such as leukemia, lymphoma, and multiple myeloma. However, there remains challenges in treating solid tumors. These challenges include physical barriers, tumor microenvironment immunosuppression, tumor heterogeneity and target specificity. Especially, due to tumor microenvironmental barriers, CAR T cells are not effectively exposed to tumor antigens and cannot activate co-stimulation signals on CAR molecules, thus conventional CAR T cell therapy has thus far shown weak cell expansion in solid tumor patients, achieved little or no therapeutic responses. Here, we developed CAR T cells based on a novel CoupledCAR® technology to overcome the lack of persistence of solid tumor CAR T cells in vivo. Methods: We designed a 'CoupledCAR' lentivirus vector containing a single-chain variable fragment (scFv) targeting human TSHR. The lentivirus was produced by transfecting HEK-293T cells with 'CoupledCAR' lentiviral vectors and viral packaging plasmids. Patient's CD3 T cells were cultured in X-VIVO medium containing 125U/mL 1interleukin-2 (IL-2), and transduced with 'CoupledCAR' lentivirus at certain MOI. Transduction efficiency and was evaluated at 7 to 9 days after 'CoupledCAR' lentivirus transduction, and quality controls for fungi, bacteria, mycoplasma, chlamydia, and endotoxin were performed. After infusion, serial peripheral blood samples were collected, and the expansion and the cytokine release of CART cells were detected by FACS and QPCR. The evaluation of response level for patients were performed at month 1, month 3, and month 6 by PET/CT. Results: We used prostatic acid phosphatase (PAP) as an exemplary CAR target for prostate cancer and demonstrated that our CoupledCAR® significantly enhanced the expansion of PAP CAR T cells in vitro and in vivo. Further, we observed that this expansion showed more memory-like phenotypes, and caused little exhaustion of PAP CAR T cells. Also, we find coupled solid tumor CAR T cells have stronger tumor killing ability. We demonstrated this simple expansion to enable the persistence of solid tumor CAR T cells and can be further applied to other kinds of T cell therapy like TCR T and TILs. Conclusions: We developed a novel platform technology (CoupledCAR®) that allows solid tumor CAR T cells to rapidly expand. This initial CAR T cell expansion enabled enhanced trafficking and infiltration of the tumor tissue whereby further cell expansion occurred and thereby achieved tumor clearance. We have carried clinical trials and obtained early promising clinical data. We will further verify the safety and efficacy of this technology in the treatment of different kinds of solid tumors in the clinic research.